Pengaruh Model Pembelajaran Demonstrasi dalam Praktik Ibadah Shalat terhadap Pengamalan dalam Kehidupan Sehari-hari: The Influence of Demonstration-Based Learning in Prayer (Shalat) Practice on Daily Religious Observance - Ipah Latipah; Yani, Ahmad; Rochman, Asep Saepul; Hariyanto, Teguh (Risalah Kharisma, 2024)
This study investigates the effectiveness of the demonstration learning model in enhancing students’ implementation of daily prayers, with a focus on 11th-grade science students at MA Muslimin Jaya Cisaat, Sukabumi. The urgency of this research arises from the observed discrepancy between students' religious knowledge and their actual prayer practices. Using a quantitative approach with a descriptive design, the study employed a saturated sample of 22 students. Data were gathered through observation, questionnaires, interviews, and documentation, and analyzed using simple linear regression. Findings reveal that the demonstration model significantly improved students’ prayer practices, contributing 67.5% to better consistency, accuracy, and understanding. These results confirm that practical, experience-based methods are more effective than theoretical approaches in religious education. The study contributes to Islamic education literature by providing empirical evidence on how demonstration-based instruction supports behavioral internalization of religious values. However, the study is limited to a single school with a small sample size, thus reducing the generalizability of its findings. Future research should expand to other Islamic practices and educational levels. The implications suggest that integrating demonstration-based learning into religious curricula can foster meaningful engagement and spiritual development among students.